The Effect Of Production Costs On Net Income In Textile And Garment Companies Listed On The Indonesian Stock Exchange - Nur Alisa; Asri Jaya; Nurlina, Nurlina (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the effect of production costs on net income in manufacturing companies in the textile and garment sub-sector listed on the Indonesia Stock Exchange. This research uses quantitative methods. The sampling method used is purposive sampling with a sample of 15 textile and garment companies. The data source used is secondary data. Data was collected using library research and documentation from financial reports published by the company. The analytical tool used is the Statistical Package for the Social Sciences (SPSS) version 25. Based on the research results, it was found that the production costs have a positive and significant effect on net profit as shown in the t-test results, the calculated t value > t table is 2.246 > 1.997 with a significant value of 0.028 < 0.05, which means Ho is rejected and Ha is accepted. So it can be concluded that production costs partially have a positive and significant effect on net profit.